Masjid dan Gereja Orang Basudara: Tradisi Damai Membangun Rumah Ibadah Salam Sarena di Maluku - Indonesia - Tubaka, Abdul Manaf (IAIN Ambon, 2023)
This research aims to explore the construction of a culture of peace in kinship relations (gandong) among the villages of Booi, Aboru, Kariu, and Hualoy (BAKH), Christian-Muslim communities, which have a culture-brotherhood narrative. Located on various islands in Central Maluku, these villages preserve the narrative of culture-brotherhood as the basis of social and religious life. Embracing different religious beliefs, the four villages celebrate cultural-kinship ties through religious symbols: churches and mosques. In 1971, the four villages built a mosque in Hualoy, a Muslim village. Even though the three have different religious beliefs, this mosque is classified as a mosque with BAKH. In the midst of the 1999 – 2004 Maluku conflict which turned Ambon, the capital of Maluku Province, into social segregation, the four villages rebuilt the Kariu church, a Christian village in 2017. Support for the construction of this church came from BAKH residents in Maluku and the diaspora. Using ethnographic methods, this research investigates the cultural narrative behind the performativity of Christians-Muslims involved in previous conflicts, but collectively rebuilding religious holy places. This research concludes that kinship cultural relationships, performative actions and shared symbols contribute to the peace building process in the post-conflict region, Maluku.Keywords: Construction, Culture of Peace, Collaboration with BAKH, Cultural and Religious Identity